Optimization of fermentation conditions for lignin peroxidase production using selected waste - Mohd Yusouf Bin Abdul Latif (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Procedures to grow and trigger secondary metabolism of white rot fungus Phanerochaete chrysosporium for lignin peroxidase (LiP) production is depending on fermentation medium formulation as well as type of growth vessel. Sewage treatment plant (STP) sludge and palm oil mill effluent (POME) were among the alternative substrates used successfully but there was no performance assessment reported. A labscale study was carried out in shake flasks to identify which one of these organic wastes produce higher LiP activity. Inoculum of P. chrysosporium (PC-2094) was fermented in liquid broth contained combination of either STP sludge or POME as major substrate, wheat flour as co-substrate, and oil palm empty fruit bunch (EFB) as lignocellulosic material supplement. Higher LiP activity was observed in POME within shorter period of fermentation as compared to STP sludge, without EFB supplement. The highest LiP enzyme activity from POME production was 8.33 U/L at day 4 while it was 5.29 U/L at day 6 in STP sludge. Therefore, POME was selected as the preferable substrate to be studied for screening and optimization. Experimental design offers a more balanced, manageable technique than one-factor-at-a-time especially when many factors are investigated for fermentation improvement study. Plackett-Burman screening design was employed to screen eleven variables including operational and nutritional factors, and three were found to be the most significant ones. The factors namely pH setting, wheat flour and potassium dihydrogen phosphate (KH2PO4) supplementation were then considered for optimization to determine their optimal setting using response surface method, as in central composite design. An 11% improvement was achieved in screening stage whereby highest activity achieved was 9.26 U/L and further improvement in activity was achieved in optimization stage, making an overall 30% increment with highest activity was 10.86 U/L. Validation experiments were carried out against the model developed to evaluate the optimum conditions and results deviated within permissible ±10% contingency of predicted values. The enzyme samples were also used for stability test and results showed that the crude enzyme was most stable at pH 5.0 and 55°C, which maintained its activity of more than 80% for up to three hours incubation time. With the findings, it may further support sustainable reuse of POME into value-added product.